Large geographic and temporal extensions of the Río de la Plata Craton, South America, and its metacratonic eastern margin - Santos, J.; Chernicoff, C.; Zappettini, E.; McNaughton, Neal; Hartmann, L. (Taylor & Francis Inc., 2019)
Integration of existing isotopic and geological data allows a reconsideration of the distribution and age of the Río de la Plata Craton within South America. The reinterpretation increases the area of the craton to about 2,400,000 km2 with implications for the tectonic map of South America and for global reconstruction of palaeocontinents. Four areas previously considered as separate cratons (Luís Alves, Curitiba, Tebicuary, and Paranapanema) are interpreted as part of the same Río de la Plata Craton. The craton is organized into six provinces and domains: Buenos Aires–Piedra Alta, Taquarembó, Tebicuary, Luís Alves, Encantadas, and Nico Pérez. The term ‘Transplatense’ is proposed to replace ‘Trans-Amazonian’ for Rhyacian events that occurred within the Río de la Plata Craton. The craton is formed not only by dominant Rhyacian rocks and local Archaean rocks, but also by Statherian and Mesoproterozoic rocks. The domains are all partially to totally covered by Phanerozoic basins (Paraná, Chacoparanense, Claromecó, Salado, Balcarce, and Colorado) which makes their investigation difficult. The Ediacaran–Cambrian collisions of the Brasilian orogen generated tectonic mixtures of orogenic and cratonic zones. This is more evident in the eastern margin of the craton, which behaved as a metacraton.